2021
DOI: 10.1128/mbio.03001-21
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Mechanism of Biodegradation and Defluorination of 2,2-Difluoro-1,3-Benzodioxole by Pseudomonas putida F1

Abstract: There are more than 9,000 polyfluorinated compounds developed for commercial use, some negatively impacting human health, and they are generally considered to be resistant to biodegradation. Only a limited number of studies have identified microbes with enzymes sufficiently reactive to defluorinate difluoromethylene carbon groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 57 publications
(66 reference statements)
0
28
0
Order By: Relevance
“…Most of these involve mono-fluorinated compounds. The complete defluorination of a difluorinated aromatic compound by Pseudomonas putida F1 was reported (Bygd et al, 2021). Most recently, an aromatic compound with four fluorine substituents has been shown to undergo defluorination (Bygd et al, 2022).…”
Section: Pseudomonas In Biodegradation and Specifically With Fluorina...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these involve mono-fluorinated compounds. The complete defluorination of a difluorinated aromatic compound by Pseudomonas putida F1 was reported (Bygd et al, 2021). Most recently, an aromatic compound with four fluorine substituents has been shown to undergo defluorination (Bygd et al, 2022).…”
Section: Pseudomonas In Biodegradation and Specifically With Fluorina...mentioning
confidence: 99%
“…Many details on the interactions of Pseudomonas with polyfluorinated alkyl, alkenyl and aryl compounds (as we have defined PFAS) have yet to be revealed. Currently, several dozen fluorinated compounds have been shown to undergo defluorination in direct experiments with different Pseudomonas strains (Goldman, 1965;Renganathan, 1989;Li and Wackett, 1993;Kim et al, 2012;Butt et al, 2014;Xie et al, 2020;Bygd et al, 2021;Bygd et al, 2022). This author expects many more to come.…”
Section: Conclusion and Promisementioning
confidence: 99%
“…A previous study showed defluorination of the difluoro-bicyclic compound, 2,2-difluoro-1,3-benzodioxole (DFBD) (Bygd et al, 2021) after inducing P. putida F1 with toluene, because previous biotransformation experiments with bicyclic ring compounds had required preinduction (Kwit et al, 2008;Wackett et al, 1988). Indeed, previous direct induction experiments with multicyclic compounds 1-naphthol, 1,2-dihydronapthalene and anthracene had shown no induction (Busch et al, 2007).…”
Section: Testing Of Polyfluorinated Benzene Compoundsmentioning
confidence: 99%
“…In previous studies on toluene dioxygenase-mediated defluorination, P. putida F1 cells were pre-incubated with toluene before transformation of the fluorinated substrate (Bygd et al, 2021(Bygd et al, , 2022. Here, we investigated whether specific fluorinated compounds would induce the tod operon enzymes, undergo metabolic transformation and defluorination as indicated by fluoride release into the F I G U R E 3 Comparison of toluene dioxygenase (TDO) induction using the 6-fluoroindole activity assay from this article (light bars) to previously published results using a β-galactosidase reporter (dark bars).…”
Section: Fluorinated Compounds Mediating Their Induction and Defluori...mentioning
confidence: 99%
See 1 more Smart Citation